PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MENGATASI MASALAH PEKERJA ANAK DI INDIA TAHUN 2020-2022 - Fadillah, Muhammad Irfan; Saeri, Mohammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Child labor remains a global issue, particularly in developing countries like India, which recorded significant child labor figures during 2020–2022. The purpose of this study is to analyze the role of the ILO in addressing child labor issues in India during the 2020–2022 period through various programs, technical cooperation, and the ratification of international conventions. This study uses a qualitative method with a descriptive approach, and data collection techniques Within the theoretical framework, this study utilizes the theory of international organizations as proposed by Clive Archer, which positions international organizations as instruments, arenas, and independent actors within the international system. This theory is relevant to examining how the ILO carries out its functions, both as a tool for member states in formulating policies, as a forum for international actors to interact, and as an independent entity capable of making its own decisions. As an instrument, the ILO runs programs such as the Measurement, Awareness Raising, and Policy Engagement (MAP16), and Policies, Partnerships, Learning & Local Empowerment (PPLL), which support education and community empowerment. As an arena, the ILO provides a forum for discussion, multilateral cooperation, and policy advocacy that encourages the ratification of international conventions related to child labor. As an independent actor, the ILO independently drafted Conventions 138 and 182 and created a specific program to address child labor issues, the International Programme on Elimination of Child Labor (IPEC). Nevertheless, this study found that fundamental challenges—primarily poverty, social inequality, and weak legal implementation—remain major obstacles to the complete elimination of child labor in India. Keywords: Child labor, International Labor Organization (ILO), India, Instruments, Arena, Independent Actors